Comparative Study of Three Traditional Mongolian Medicines on Streptozotocin-induced Diabetic Nephropathy in Rats - Wang, X.-L.; Liji, A.; Liu, J.; Wang, X.-Z.; Wei, C.-X. (Drug Research, 2015)
3 kinds of prescription of Traditional Mongolian (Chinese) Medicine (TMM) have been used in treating diabetic nephropathy (DN). We aimed to investigate: first, which prescription was more effective; second, whether it was more effective when combined with the 3 prescriptions. The DN model was prepared by a single dose of Streptozotocin (STZ, 65 mg/kg, i.p.) in rats and treated 3 times every day with P-1 (Sugmul-10), P-2 (Narenmandul-11), P-3 (Xieriga-4) respectively, and combined group was treated with P-1 in the morning, P-2 and P-3 in the evening. The results showed combining with 3 prescriptions in one day was much more effective than each single prescription. The mechanism of renal protection maybe related to MMP-2 and TGF-β1, the conclusion could be useful and beneficial for clinical medicine.
Keywords: Sugmul-10; Narenmandul-11; Xieriga-4; diabetic nephropathy; renal function